TRAGOM PUŽEVA OD OBALE KA UNUTRAŠNJOSTI I NATRAG: PROBUŠENI MORSKI I SLATKOVODNI PUŽEVI KAO POKAZATELJ REGIONALNIH SUSTAVA RAZMJENE TIJEKOM MEZOLITIKA U HRVATSKOJ. - KOMŠO, Darko; VUKOSAVLJEVIĆ, Nikola; KARAVANIĆ, Ivor; MIRACLE, Preston (Histria Archaeologica, 2019)
Perforated shells figure prominently in discussions of exchange systems and body ornamentation during the Mesolithic in Europe. In this paper we discuss assemblages of perforated snail shells recovered from recent excavations of Mesolithic sites in Croatia. Numerous finds are found in several sites in Northern Adriatic and in Zala Cave in Croatia’s inland region of Ogulin-Plaški intermountain valley. Perforated marine and freshwater snail shells from both regions suggest the existence of regional exchange systems during the Mesolithic between coastal and inland areas.